2020
DOI: 10.1016/j.resconrec.2020.104854
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sustainability assessment of household food waste management in the Amsterdam Metropolitan Area

Abstract: Highlights Multi-fold local & global data collected and processed into a comprehensive framework Anaerobic digestion with effective nutrient recovery appears the best option All alternative strategies to incineration increase food waste management costs Aggregation makes findings accessible to the widest possible audience and stakeholder The study informs stakeholders and authorities on the consequences of their options Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…MSWI produces many harmful substances such as heavy metal, dioxin, smoke dust, and so on. If these harmful substances cannot be handled well, they will cause secondary pollution to the environment [55,56]. e flue gas needs to be purified by different types of reaction towers.…”
Section: Mswi Processmentioning
confidence: 99%
“…MSWI produces many harmful substances such as heavy metal, dioxin, smoke dust, and so on. If these harmful substances cannot be handled well, they will cause secondary pollution to the environment [55,56]. e flue gas needs to be purified by different types of reaction towers.…”
Section: Mswi Processmentioning
confidence: 99%
“…It provides sustainable development advantages to the city, leading to progressive change toward low-carbon, resource-efficiency, resilience, and sustainable communities [52]. Studies confirm the reduction of the negative impact of inappropriate waste management landfill sites [53], reduce transportation and operational costs, and has significantly less CH4 gas emissions [54]. After a maturation process, the product being obtained using the technology presented in the article can be used as a soil amendment, bringing benefits on resource consumption and an increase in agricultural productivity [55,56].…”
Section: Final Considerations Of the Proposed Technological Solution ...mentioning
confidence: 98%
“…Composting of food waste encounters a number of technical challenges, arising weak physical structure of food waste with weak porosity, high content of water, low carbon-to-nitrogen relation and fast hydrolysis and accumulation of organic acids during composting (Voberkova et al, 2020). Anaerobic digestion coupled with effective nutrient and energy recovery appears to be the preferred option to improve the overall sustainability of household food waste management in Amsterdam (Tonini et al, 2020). Kucbel et al (2019) reported that composts household food waste has low stabilization of organic components.…”
Section: Urban Food Waste Compostingmentioning
confidence: 99%